2007
DOI: 10.1093/humrep/dem172
|View full text |Cite
|
Sign up to set email alerts
|

Infertility, assisted reproduction technologies and imprinting disturbances: a Dutch study

Abstract: After correction for the increased fertility problems of the parents, there is no increased incidence of ART related birth of AS, PWS or BWS children. ART does not seem to have a direct effect on the increase of imprinted diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
2
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(173 citation statements)
references
References 18 publications
5
160
2
6
Order By: Relevance
“…A study conducted by Doornbos et al found that an increased incidence of imprinting diseases was associated with increased fertility problems of the parents but not ART (39). Particularly, the intrinsic imprinting defects of spermatozoa appeared to be responsible for the increased incidence of imprinting disorders (37).…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted by Doornbos et al found that an increased incidence of imprinting diseases was associated with increased fertility problems of the parents but not ART (39). Particularly, the intrinsic imprinting defects of spermatozoa appeared to be responsible for the increased incidence of imprinting disorders (37).…”
Section: Discussionmentioning
confidence: 97%
“…Advanced maternal age (O35 years) is directly related to a decline in fertility with a reduced oocyte reserve and poor oocyte quality (Liu & Case 2011). In a Dutch study evaluating ARTs and parental infertility, 6.3% of AS, 8.5% of BWS, and 2.1% of total children were conceived via ARTs, while 6.3% of AS, 8.5% of BWS, and 3.5% of total children were born to subfertile families without ARTs (Doornbos et al 2007; Table 6). …”
Section: Female Infertility/subfertilitymentioning
confidence: 99%
“…A study of sporadic PWS cases found that 9 of the 163 PWS patients were conceived by ART (2 using ICSI and 7 using fertility drugs) and two of the patients were found to have a chromosome deletion (Sutcliffe et al, 2006). Another study showed that 4 of 86 PWS patients were conceived using various forms and 1 using ovulation induction) (Doornbos et al, 2007). On the other hand, Lidegaard et al any cases of PWS in 6,052 children conceived by ART.…”
Section: Art and Birth Defectsmentioning
confidence: 99%